Back Cover: Chemical‐Bonding‐Directed Hierarchical Assembly of Nanoribbon‐Shaped Nanocomposites of Gold Nanorods and Poly(3‐hexylthiophene) (Angew. Chem. Int. Ed. 30/2016). Issue 30 (12th May 2016) - Pan, Shuang; He, Luze; Peng, Juan; Qiu, Feng; Lin, Zhiqun
Abstract : Ants, mimicking gold nanorods (AuNRs) are attracted by sugar, or in this case, thiol‐terminated poly(3‐hexylthiophene) (P3HT) nanofibers. In their Communication onpage 8686 ff., J. Peng, Z. Lin, and co‐workers describe a facile bottom‐up co‐assembly strategy for crafting hierarchical nanoribbon‐shaped P3HT/AuNR nanocomposites composed of P3HT‐SH nanoribbons with AuNRs aligned on the surface of the nanoribbon.